2015
DOI: 10.3904/kjim.2015.30.6.856
|View full text |Cite
|
Sign up to set email alerts
|

Predicting postoperative total calcium requirements after parathyroidectomy in secondary hyperparathyroidism

Abstract: Background/Aims:To prevent hypocalcemia after parathyroidectomy (PTX), parenteral calcium is required in addition to oral calcitriol and calcium. After switching to oral calcium, patients can be discharged from the hospital. The aim of this study was to analyze the clinical characteristics and outcomes of PTX performed at a single Korean center and to investigate the associated laboratory factors used to analyze the total amount of postoperative calcium required. Methods:We enrolled 91 hemodialysis patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…The cutoff point may help to prevent hypocalcemia by predicting insufficient calcium supplements when patients have been administrated calcium as per the formula protocol. The formula for the postoperative calcium requirement after parathyroidectomy contributes to preventing prolonged hypocalcemia safely . In the present study, the first equation was helpful for the calcium supplements to prevent hypocalcemia in the second phase.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The cutoff point may help to prevent hypocalcemia by predicting insufficient calcium supplements when patients have been administrated calcium as per the formula protocol. The formula for the postoperative calcium requirement after parathyroidectomy contributes to preventing prolonged hypocalcemia safely . In the present study, the first equation was helpful for the calcium supplements to prevent hypocalcemia in the second phase.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, the prediction of total calcium requirement after parathyroidectomy becomes important for decreasing the duration of the hospital stay and calcium balance. Few studies showed that the preoperative alkaline phosphatase level and the PTH level could be used to predict the total elemental calcium requirement after parathyroidectomy . The amount of calcium supplement and baseline characteristics showed wide differences among the studies, including the operation, preoperative serum PTH levels, and serum alkaline phosphatase levels (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, Byung et al reported that preoperative alkaline phosphatase, preoperative intact parathyroid hormone and phosphorus at 48 hours may be significant factors in estimating the postoperative calcium requirement after parathyroidectomy. 36 However, Goldfarbyoung et al pointed out that the only identifiable preoperative risk factor for hungry bone syndrome was young age. 33 According to the pathophysiological mechanism, post-parathyroidectomy hypocalcaemia is an increased shift of calcium from the circulation to the bone tissues.…”
mentioning
confidence: 99%